2022
DOI: 10.3390/app12020869
|View full text |Cite
|
Sign up to set email alerts
|

Anodic Alumina Membranes: From Electrochemical Growth to Use as Template for Fabrication of Nanostructured Electrodes

Abstract: The great success of anodic alumina membranes is due to their morphological features coupled to both thermal and chemical stability. The electrochemical fabrication allows accurate control of the porous structure: in fact, the membrane morphological characteristics (pore length, pore diameter and cell density) can be controlled by adjusting the anodizing parameters (bath, temperature, voltage and time). This article deals with both the fabrication and use of anodic alumina membranes. In particular, we will sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 82 publications
0
10
0
Order By: Relevance
“…The fabrication procedure for nanowires of the Pd–Co alloy is detailed in [ 53 ]. The results showed that depending on the deposition conditions, it was possible to obtain arrays of both nanowires and nanotubes, and, as we have also shown in this work, it was possible to obtain both palladium-rich crystalline alloys and amorphous alloys rich in Co.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fabrication procedure for nanowires of the Pd–Co alloy is detailed in [ 53 ]. The results showed that depending on the deposition conditions, it was possible to obtain arrays of both nanowires and nanotubes, and, as we have also shown in this work, it was possible to obtain both palladium-rich crystalline alloys and amorphous alloys rich in Co.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of deposits on CP, in fact, the alloys with this composition showed the best performances. According to the results discussed above, an array rich in Co is obtained when a dilute solution of palladium is used [ 53 ]. Also in this case, the alloy was found to be amorphous and the electrodes consisted of cylindrical nanowires (length around 4.5 μm), which replicated the morphology of pores of the alumina template.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 The preparation of AAO film is observably simple compared to the costly etched templates, 19 as well as its growth technology has been greatly improved after nearly forty years of development. [19][20][21][22][23] Many factors affecting the high-quality growth of AAO, such as aluminum crystal orientation, 24 anodization parameters, 20,[25][26][27] solution additives 28 and chemical treatment methods, 27 have been extensively and deeply studied. Recent researches have shown that it is possible to control the size of the pores by controlling different parameters of the anodizing process, [19][20][21][22]25,26,28 which is very beneficial for the implementation of SiNPs with different sizes.…”
mentioning
confidence: 99%